PEMBELAJARAN NOTASI BALOK MELALUI METODE DRILL DI SMP NEGERI 1 SUNGAI SARIAK KABUPATEN PADANGPARIAMAN - Arneti Arneti; Jagar Lumban Toruan; Syeilendra Syeilendra (SENDRATASIK UNP, 2013)
Abstract   This research aimed at describing the learning of musical notations through drilling, in the Art and Culture subject at SMP Negeri I Kabupaten Padang Pariaman. The learning of musical notations was not fully enjoyed by the students. They assumed that this learning material was difficult to understand and not really important for them. In fact, this learning material improved their ability when they later had musical, vocal. and instrumental practices. The teacher then found some solutions to solve this problem: I) explaining the form and the value of notes to the students such as about the symbol and the duration of full notes, half notes, quarter notes, and eighth notes: 2) explaining and providing examples or beats to the students such as quarter beats or eighth heats: 3) explaining the relationship of time signature (in meters) and heats such as second, third. and fourth meter: 4) explaining the differences of low and up beats and providing examples on how to read the first, second, third, and fourth notes: 5) explaining, and providing examples of units or groups of note: 6) providing examples of' rhythm patterns from the song that was taught to the students as welI as providing examples of rhythm patterns for each phrase of the song.   Keywords: Learning, Musical Notations, the Drilling Method